Effect of surface cleaning on contact resistivity of amorphous GeCu2Te3 to a W electrode. Issue 39 (3rd May 2016) - Shindo, S.; Sutou, Y.; Koike, J.; Saito, Y.; Song, Y.-H.
ABSTRACT: The contact resistivity, ρ c, between phase change material (PCM) and an electrode plays an important role in the operation of highly scaled phase change random access memory (PCRAM). We investigated the effect of surface cleaning on the ρ c between a W electrode and amorphous GeCu2 Te3 (GCT) which shows high thermal stability. The surface cleaning of the amorphous GCT was conducted by Ar reverse sputtering. The ρ c of the amorphous GCT whose surface was cleaned with Ar reverse sputtering was 6.7×10 -3 Ω cm 2 . Meanwhile, the ρ c of the amorphous GCT with no surface cleaning was 8.0×10 -5 Ω cm 2 . The low ρ c in the amorphous GCT with no surface cleaning was apparently due to the existence of a low resistance Cu-rich underlayer which was formed as a consequence of surface oxidation of the amorphous GCT. These results indicate that the surface of a PCM must be treated carefully to accurately measure the contact resistivity between the PCM and electrodes.